Новый вид рода Apista из предгорьев хребта Терскей-Алатау (Центральный Тянь-Шань) - Фалькович М.И. (Вестник зоологии, 1993)
Apista uroxella sp. n. is described from Przhevalsk vicinities (eastern shore of Issyk-Kul lake) as compared with A. callipepla F I k v. and A. adelpha F 1 k v. Type material is deposited in collection of Zoological Institute. Russian Academy of Sciences (St.-Petersburg).